Cumulative Impact of Cardiovascular Risk Factors on Regional Left Ventricular Function and Reserve: Progressive Long-Axis Dysfunction with Compensatory Radial Changes - Vinereanu, Dragos; Mädler, Christopher F.; Gherghinescu, Carmen; Ciobanu, Andrea Olivia; Fraser, Alan G. (Echocardiography (Mount Kisco, N.Y.), 2011)
Background: The risk factors that contribute to atherosclerosis also predict clinical heart failure, but it is unclear how they affect myocardial function. Aims were to assess if major cardiovascular risk factors cause subclinical myocardial dysfunction in asymptomatic subjects. Methods: We measured regional left ventricular (LV) function at rest and during dobutamine stress echocardiography in 246 subjects (54 ± 12 years, 54% men) analyzed in five groups according to the presence of six risk factors (diabetes, hypertension, obesity, dyslipidemia, smoking, and family history; age was similar in the five groups). LV longitudinal function was assessed from the mean velocities of four basal segments, and radial function from the velocities of the basal posterior wall. Results: Risk factors did not affect LV ejection fraction, but longitudinal systolic velocity decreased progressively with the number of risk factors, at rest (6.8 ± 1.3 vs. 6.2 ± 1.6 vs. 5.8 ± 1.5 vs. 5.4 ± 1.3 vs. 5.3 ± 1.3 cm/sec, for the five groups, respectively) and at peak stress (14.3 ± 3.3 vs. 12.9 ± 3.2 vs. 11.8 ± 3.4 vs. 11.3 ± 2.6 vs. 11.1 ± 2.3 cm/sec) (both P < 0.0001). Radial systolic velocity increased according to the number of risk factors (P < 0.01). By multivariate regression, determinants of reduced longitudinal systolic velocity at rest were body mass index, diastolic blood pressure, age, and fasting plasma glucose (r = 0.57, r2= 0.32, P < 0.0001). Conclusion: Asymptomatic subjects have impaired LV long‐axis function at rest and during stress, according to their number of major cardiovascular risk factors. Global LV systolic function is maintained by compensatory increases in radial function. These changes provide new targets for preclinical diagnosis and for monitoring responses to preventive strategies. (Echocardiography 2011;28:813‐820)